A Study on the Evolution of Music Curriculum Standards for Compulsory Education in China in the 21st Century - Zhang, Ruoye (Journal of Educational Research and Policies, 2025)
Since the 21st century, with the deepening of education reform, the concept of quality education has become more popular. Against this background, music education has received unprecedented attention and focus. The Ministry of Education (MOE) has issued a number of regulations and documents on music education at the compulsory education stage. Namely: the Compulsory Education Music Curriculum Standards (Experimental Draft), the Compulsory Education Music Curriculum Standards (2011 Edition), and the Compulsory Education Art Curriculum Standards (2022 Edition). The introduction of these curriculum standards has effectively promoted the development of compulsory education in this century, and further promoted the reform of national basic music education. By comparing the different versions of music curriculum standards and climbing through the revision logic of the standards, it is conducive to a comprehensive understanding of the background and details of the implementation of the curriculum.